PENGARUH KUALITAS PELAYANAN TRANSPORTASI ONLINE TERHADAP KEPUASAN PELANGGAN GOJEK (Studi Kasus Pada Pelanggan Gojek Mahasiswa FKIP UNIS) - Widiarti, Aniek (Universitas Islam Syekh Yusuf, 2022)
Abstract This study aims to determine the effect of the quality of service provided by the Gojek company on customersatisfaction among students of FKIP Islamic University Syekh-Yusuf Tangerang. Data collection was carried out by distributing questionnaires to 100 FKIP students who were Gojek customers, which were described according to gender, age, study program, domicile, type of Gojek service, and frequency of using Gojek services. This study uses twovariables, namely the service quality variable as the independent variable (free) and the customer satisfaction variable as the dependent variable (bound). The research method used in this research is quantitative method. The data analysis technique in this study used a simple regression analysis method, and the results showed that there was apositive effect of service quality on Gojek's customer satisfaction. Keywords: Customer Satisfaction, Service Quality, Gojek.